Separation of Zinc Chloride (ZnCl2) Metal Using Membrane Process - Mohamad Hazeem Bin Mohd, Mohamad Hazeem (Universiti Teknologi Petronas, 2010)
Nowadays, heavy metals are widely utilized as a main material to produce catalyst in petrochemical industry and they are also very harmful chemical substance that needs to be treated before can be discharged. The objective of this research is to investigate the separation behavior of heavy metal using membrane process. In this study, three commercial membranes; AFC 99 (Reverse Osmosis-RO), AFC40 (Nanofiltration-NF) and CA 202 (Ultrafiltration-UF) membranes were tested to determine the flux and salt rejection in aqueous solution. Zinc chloride (ZnCl2) was used in the experiments to prepare the aqueous solution. Effects of cross flow velocity, pressure, types of membranes and feed concentration towards the flux and salt rejection of those membranes were investigated. Experiments showed that the cross flow velocities had a significant effect on permeate flux values. In addition, the permeate flux increases almost in linear form as the cross flow velocity increased. Similarly, permeate flux increased as operating pressure was increased. Other parameters that affect the flux are types of membrane. From the result, the CA 202 membrane produced the highest flux followed by AFC 40 and AFC 99 respectively. For concentration effect, the flux decreased with increasing of ZnCl2 concentration. Variations in pressure and cross flow velocity also affected the salt rejection, which decreased with increasing of feed concentration. Salt rejection at low cross flow velocities was lower than those conducted at high cross flow velocities and independent of the pressure. From the experiment, the AFC 99 has the highest rejection recorded which was 98% followed by AFC 40 (84%) and CA 202 (58%) membranes respectively. This work shows that the membrane separation processes, particularly AFC 99 (RO), can be used to selectively remove ZnCl2 from wastewater.